A cross-sectional study exploring the relationship between burnout, absenteeism, and job performance among American nurses - Liselotte N. Dyrbye; Tait D. Shanafelt; Pamela O. Johnson; Le Ann Johnson; Daniel Satele; Colin P. West (BMC, 2019)
Abstract Background Studies suggest a high prevalence of burnout among nurses. The aim of this study was to evaluate the relationship between burnout among nurses and absenteeism and work performance. Methods A national sample of U.S. nurses was sent an anonymous, cross-sectional survey in 2016. The survey included items about demographics, fatigue, and validated instruments to measure burnout, absenteeism, and poor work performance in the last month. Results Of the 3098 nurses who received the survey, 812 (26.2%) responded. The mean age was 52.3 years (SD 12.5), nearly all were women (94.5%) and most were married (61.9%) and had a child (75.2%). Participating nurses had a mean of 25.7 (SD 13.9) years of experience working as nurse and most held a baccalaureate (38.2%) or masters of science (37.1%) degree in nursing. A quarter worked in the inpatient setting (25.5%) and the average hours worked per week was 41.3 (SD 14.1). Overall, 35.3% had symptoms of burnout, 30.7% had symptoms of depression, 8.3% had been absent 1 or more days in the last month due to personal health, and 43.8% had poor work performance in the last month. Nurses who had burnout were more likely to have been absent 1 or more days in the last month (OR 1.85, 95% CI 1.25-2.72) and have poor work performance (referent: high performer; medium performer, OR 2.68,95% CI 1.82-3.99; poor performer, OR 5.01, 95% CI 3.09-8.14). After adjusting for age, sex, relationship and parental status, highest academic degree, practice setting, burnout, depression, and satisfaction with work-life integration, nurses who were more fatigued (for each point worsening, OR 1.22, 95% CI 1.10-1.37) were more likely to have had absenteeism while those who worked more hours (for each additional hour OR 0.98, 95% CI 0.96-1.00) were less likely to have had absenteeism. Factors independently associated with poor work performance included burnout (OR 2.15, 95% CI 1.43-3.24) and fatigue (for each point of worsening, OR 1.22, 95% CI 1.12-1.33). Conclusions These findings suggest burnout is prevalent among nurses and likely impacts work performance.